Kinetic study of SO2 with sodium lactate based deep eutectic solvents and modelling of desulfurization intensification in rotating packed bed reactor. (2nd February 2022) - Dong, Yu-Ning; Chen, Wen-Cong; Zhang, Liang-Liang; Sun, Bao-Chang; Chu, Guang-Wen; Chen, Jian-Feng
Highlights: The reaction kinetics of SO2 and NaLa/water DES was firstly studied. Desulfurization by NaLa/water DES was intensified by rotating packed bed (RPB). A mathematic model was developed to describe the mass transfer process in RPB. A satisfactory agreement was obtained between experimental and modeling results. Abstract: As ionic liquids alternative, the deep eutectic solvents (DESs) are expected to realize green and efficient SO2 recovery. In this work, the reaction kinetics of SO2 and sodium lactate (NaLa)/water DES was first studied. The reaction kinetic parameters, including order of reaction, rate constant, pre-exponential factor, and activation energy were determined. In view of the reaction characteristics, desulfurization intensification by high gravity technology was proposed. A mathematic model based on the reaction kinetics was developed to describe the SO2 -DES mass transfer and reaction process in a rotating packed bed reactor. To validate this model, the desulfurization efficiency and mass transfer coefficient were measured under different operating conditions. It was demonstrated that SO2 removal efficiency was above 99% under optimized conditions, realizing efficient SO2 recovery. The validity of the proposed model was confirmed by the fact that most predicted mass transfer coefficients agreed well with the experimental results with deviations within ± 15%.